2015
DOI: 10.1099/jgv.0.000313
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-infected cells release Fas ligand in exosomal fractions and induce apoptosis in recipient cells via the extrinsic pathway

Abstract: Epstein-Barr virus (EBV; human herpesvirus 4) is an oncogenic herpesvirus implicated in the pathogenesis of several human malignancies. A number of recent studies indicate that EBV can manipulate the local microenvironment by excreting viral and cellular components in nanovesicles called exosomes. In this study, we investigated the impact of EBV-derived exosomes on apoptosis of recipient cells and the molecular pathway involved in this process. Exosomes from EBV-infected but not from non-infected cells induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…VZV can cause chickenpox among the elderly and immunocompromised individuals during acute infection (Ahmed et al, 2015). Although primary chickenpox is typically self-limited, VZV can remain dormant in the nervous system and then is reactivated in a weak host, leading to shingles or inflammation (Kurapati et al, 2017).…”
Section: Exosomes In Alpha Herpesvirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…VZV can cause chickenpox among the elderly and immunocompromised individuals during acute infection (Ahmed et al, 2015). Although primary chickenpox is typically self-limited, VZV can remain dormant in the nervous system and then is reactivated in a weak host, leading to shingles or inflammation (Kurapati et al, 2017).…”
Section: Exosomes In Alpha Herpesvirus Infectionmentioning
confidence: 99%
“…Moreover, CD63 is a critical partner of LMP1 to enhance exosome production and limit the activation of downstream signaling pathways such as NF-κB (Hurwitz et al, 2016). In addition, EBVinfected cells influence recipient cells and the surrounding microenvironment through exosomal miRNAs, Fas ligand, EBERs and other non-coding RNAs (Ahmed et al, 2015;Dolcetti, 2015;Iwakiri, 2015;Baglio et al, 2016;Gallo et al, 2016;Lin et al, 2016;Yoon et al, 2016;Zuo et al, 2017). MiRNAs are regarded as essential mediators in a variety of processes by orchestrating distinct targets and molecular pathways, and they are involved in immunological activities such as congenital immunity and virus infection Jia et al, 2014).…”
Section: Exosomes In Gamma Herpesvirus Infectionmentioning
confidence: 99%
“…80,81 The major EBV oncoprotein LMP-1 can be detected in EBV exosomes and may inhibit both T-cell and natural killer cell responses in vitro through the strong immunosuppressive properties of a conserved region within the first transmembrane domain of LMP-1. 82 EBV-infected B cells were also shown to produce and release FasL1 exosomes that have the capacity to kill antigen-specific T cells, 83,84 an effect that could contribute to keep immune effectors away from tumor cells. EBV exosomes also contain deoxyuridine triphosphate nucleotidohydrolase (dUTPase), a protein encoded by the BLLF3 EBV gene expressed during abortive or lytic replication, which may interfere with both innate and adaptive immune responses.…”
Section: Microenvironmental Impact Of Ebv Infectionmentioning
confidence: 99%
“…85 Baglio et al 107 showed that virus-modified exosomes also have a physiological role in the establishment of a life-long asymptomatic latent infection. Viral exosome-mediated immunity dysfunction has also been reported in other disorders recently.…”
Section: Potential Roles Of Exosomes In Virus-related Lymphomasmentioning
confidence: 99%
“…81,82 For instance, previous evidence pointed toward Fas ligand (FasL)-positive microvesicles as the mediator of inhibiting immune responses by inducing T-cell apoptosis. 83,84 Recently, Ahmed et al 85 showed that Epstein-Barr virus (EBV), implicated in several types of lymphomas, could hijack the exosomes to induce apoptosis in a large number of cell types, including T-cells, B-cells, and epithelial cells, possibly led to T-cell depression.…”
Section: Lymphoma Exosomes Participate In Antitumor Effect and Immunementioning
confidence: 99%